Сутність договорів, які укладаються з метою здійснення корпоративного інвестування - Кухарєв, О. Є.; Kukhariev, O. Ye. (Вісник Харківського національного університету внутрішніх справ. – 2023. – № 4 (103). - С. 80-90, 2023)
Статтю присвячено з’ясуванню сутності договорів у сфері корпоративного інвестування. Наголошено, що інвестиційні договори охоплюють різні види цивільно-правових договорів. Сферою застосування досліджуваних договорів є корпоративні правовідносини, тобто відносини, пов’язані зі здійсненням корпоративних прав на участь в управлінні господарською організацією. Сторонами договору у сфері корпоративного інвестування є суб’єкти інвестиційної діяльності, до яких належить передусім інвестор, тобто суб’єкт інвестиційної діяльності, який приймає рішення про вкладення власних, позичкових і залучених майнових та інтелектуальних цінностей в об’єкти інвестування. Іншою стороною договору можуть бути, зокрема, корпоративний фонд, компанія з управління активами як реципієнти інвестицій. Такі договори не об’єднуються спільним предметом, який зумовлений конкретним видом інвестиційного договору (дії з управління активами, частка в статутному (складеному) капіталі господарського товариства тощо). Договори, які укладаються з метою здійснення корпоративного інвестування, є консенсуальними, оплатними та двосторонніми.

The article is focused on clarifying the essence of contracts in the field of corporate investment. Achieving the specified purpose is realized through the analysis of the relevant norms of the current legislation of Ukraine, court case-law and provisions of the legal doctrine, which is the objective of this article. It has been emphasized that investment contracts cover various types of civil contracts. It has been determined by the subject matter and objectives of investment (joint operation agreements, capital construction contracts, credit granting agreements, purchase and sale agreements, fiduciary management agreements). The contract is the main form of investing in the field of corporate legal relations. The author has substantiated the specific features of such a contract, which are: the special sphere of its application; special contracting parties. The sphere of application of the contracts studied in the article is corporate legal relations, that is, relations connected to the exercise of corporate rights to participate in the management of a business entity. The parties to the contract in the field of corporate investment are the subjects of investment operation, which primarily include: an investor, i.e., the subject of investment operation that makes a decision to invest own, loaned and borrowed property and intellectual values into investment objects. The other party to the contract can be, in particular, a corporate fund, assets management company as recipients of investments. Such contracts are not united by a common subject matter, which is determined by a specific type of investment contract (asset management actions, a share in the authorized (joint) capital of a business entity, etc.). Therefore, the author has emphasized the impracticality of uniting contracts in the field of corporate investment into a separate group of civil contracts. Contracts concluded for the purpose of implementing corporate investment are consensual, commutative and bilateral.

Статья посвящена выяснению сущности договоров в сфере корпоративного инвестирования. Отмечено, что инвестиционные договоры охватывают разные виды гражданско-правовых договоров. Сферой применения изучаемых договоров являются корпоративные правоотношения, то есть отношения, связанные с осуществлением корпоративных прав на участие в управлении хозяйственной организацией.
Essence of contracts concluded for implementing corporate investment
Keywords: договір; інвестиційний договір; інвестиції; інвестиційна діяльність; корпоративні правовідносини; інвестиційний фонд; корпоративне інвестування; contract; investment contract; investments; investment operation; corporate legal relations; equity fund; corporate investment; договор; инвестиционный договор; инвестиции; инвестиционная деятельность; корпоративное правоотношение; инвестиционный фонд; корпоративное инвестирование